Virtual Enframing: Social Media's Subsumption of the Other in Theyness - McKerracher, David (Stance: an international undergraduate philosophy journal, 2017)
Sherry Turkle’s “virtuous circle” will be used to bring insights from Heidegger and Levinas into accord. Turkle argues that the distraction and escape made possible by our devices tend to undermine achieving solitude and genuine sociality, thus posing a danger to the interdependent possibilities of authenticity and ethical living. For Heidegger, the call of conscience is one’s ownmost possibility, death. Levinas argues that the call of conscience is instead ethical, instigated by the face of the Other. Rather than conflicting, these two phenomenological accounts of conscience will be shown to be mutually affirming once brought into harmony via Turkle’s framework.